PENERAPAN FRAUD PENTAGON THEORY DALAM MENDETEKSI POTENSI KECURANGAN LAPORAN KEUANGAN DENGAN KOMITE AUDIT SEBAGAI MODERASI - Rifka Annur Lestari; Tarmizi Achmad (Diponegoro Journal of Accounting, 2025)
Financial statement fraud is a crucial issue that can cause losses for stakeholders. This study aims to analyze the influence of the fraud pentagon theory on the likelihood of financial reporting fraud. The objects of this study are companies in the healthcare industry listed on the Indonesia Stock Exchange (IDX) during the period 2020-2024. Additionally, this study also examines the role of audit committee competence as a moderating variable. This study uses independent variables consisting of pressure, opportunity, rationalization, capability, and arrogance, with financial statement fraud as the dependent variable, and the audit committee as the moderating variable. A quantitative approach was applied in this study, with secondary data analyzed using logistic regression and Moderated Regression Analysis (MRA). The results of the study indicate that pressure and opportunity, which are part of the fraud pentagon theory, have a significant effect on the potential for financial statement fraud. Additionally, the existence of an audit committee with competence in accounting and finance has been proven to weaken pressure and opportunity.